Experimental investigation of a near-field focusing performance of the IP-Dip polymer based 2D and 3D Fresnel zone plate geometries fabricated using 3D laser lithography coated with hyperbolic dispersion surface layered metamaterial - Micek Patrik; Belosludtsev Alexandr; Gric Tatjana; Pudis Dusan; Gaso Peter; Goraus Matej (Nanophotonics)
Herein we investigate the character of the near-field emission of a two- (2D) and novel three-dimensional (3D) probe geometries fabricated using 3D direct laser writing lithography. Near-field scans in x–y and y–z planes were measured both before and after the deposition of hyperbolic dispersion metamaterial (HMM) to further verify the directional propagation of the high wave-vector components present in the vicinity of the structures. Additional computational and theoretical characterization forewent the actual experimental measurements, showing a promising performance, particularly for the 3D Fresnel zone plate (FZP). Overall, the experimental data documents a subwavelength resolution with a significant signal enhancement in the focal spot of the 3D FZP and highly subwavelength depth of focus.